2020
DOI: 10.1186/s12887-020-1937-1
|View full text |Cite
|
Sign up to set email alerts
|

Children still experience pain during hospital stay: a cross-sectional study from four countries in Europe

Abstract: Background: Little is known whether children experience pain during hospital stay from the child's own perspective or not. The existing studies tend to be based on a small number of children and therefore have limitations concerning the generalisability of the results. Aim: The aim of this study was to describe children's self-reported pain and experience concerning pain management during hospital stay. Methods: This study has a quantitative cross-sectional design with descriptive statistics as data analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…Furthermore, when the assessment was conducted, no invasive procedures associated with pain were performed, such as blood tests and punctures, inter alia. The relevance of these procedures has been highlighted in pain prevalence studies that assessed spontaneous patient reports, where two thirds of the children expressed pain during hospitalization (7). Additionally, LLANTO should be administered in a controlled environment and this in itself introduces a potential bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when the assessment was conducted, no invasive procedures associated with pain were performed, such as blood tests and punctures, inter alia. The relevance of these procedures has been highlighted in pain prevalence studies that assessed spontaneous patient reports, where two thirds of the children expressed pain during hospitalization (7). Additionally, LLANTO should be administered in a controlled environment and this in itself introduces a potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is a sensory and emotional experience associated with an actual or potential injury (1); it involves biological, cognitive and social components (2,3). It is a frequent condition among the hospitalized pediatric population (4,5), and usually the assessment and management is not optimal (6)(7)(8)(9)(10). It has been said that pain assessment and management in infants and preschool children is challenging due to the cognitive characteristics of this population (11).…”
Section: Introductionmentioning
confidence: 99%
“…None of the existing scales are adapted to all ages (Tsze et al, 2013) and therefore there is still a need to develop pain assessment scales, especially for younger children (Von Baeyer et al, 2017). The pain assessment scales are constantly evolving; there is, for example, a revised version of FLACC, r-FLCC, but it has not been validated in a Swedish context (Nilsson, 2016;Voepel-Lewis et al, 2008). In pediatrics that includes children of different ages (in Sweden 0-18 years) and requirements for self-assessment of pain as far as possible, the challenge for nurses will continue to exist, but with more education and regular use of selected pain scales, the work with pain assessments can be facilitated and reduce these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Even though research has been able to show the importance of pain assessment, adequate recommendations for both acute and chronic pain are still missing within Swedish health care (Alfvén et al, 2012). A recent study by Vejzovic et al (2020) has also shown that children as inpatients still experience pain during hospitalization.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation